PENGABDIAN KEPADA MASYARAKAT MELALUI KEGIATAN KEAGAMAAN, SOSIAL, DAN BUDAYA DI BEBERAPA PURA DI JAWA TIMUR - Putri Anggreni; I Gusti Ayu Suasthi; Wayan Paramartha (JURNAL SEWAKA BHAKTI, 2026)
Community service activities are one of the manifestations of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education), which aim to make a tangible contribution to society. One form of service that is relevant to the local wisdom of the Balinese people is religious and social activities at several temples in East Java. These activities include participations in communal prayers, "ngayah" activities, and education on spiritual and social values for the community. This community service aims to increase spiritual awareness, strengthen social solidarity, and preserve Hindu culture and religious traditions. The method used is a participatory approach that directly involves the community. The results of the activities show an increase in community participation, a growing sense of togetherness, and better understanding of the meaning of religious activities at temples. These activities are expected to become a model for community service based on culture and local wisdom.